Requirement of Histone Deacetylase 6 for Interleukin-6 Induced Epithelial-Mesenchymal Transition, Proliferation, and Migration of Peritoneal Mesothelial Cells - Shi, Yingfeng; Tao, Min; Ni, Jun; Tang, Lunxian; Liu, Feng; Chen, Hui; Ma, Xiaoyan; Hu, Yan; Zhou, Xun; Qiu, Andong; Zhuang, Shougang; Liu, Na (Frontiers in Pharmacology, 2021)
Aims: Influenced by microenvironment, human peritoneal mesothelial cells (HPMCs) acquired fibrotic phenotype, which was identified as the protagonist for peritoneal fibrosis. In this study, we examined the role of histone deacetylase 6 (HDAC6) for interleukin-6 (IL-6) induced epithelial-mesenchymal transition (EMT), proliferation and migration of HPMCs. Methods: The role of HDAC6 in IL-6-elicited EMT of HPMCs was tested by morphological observation of light microscope, immunoblotting and immune-fluorescence assay. And the function of HDAC6 in proliferation and migration of HPMCs was examined by CCK-8 assay, wound healing experiment and immunoblotting. Results: IL-6 stimulation significantly increased the expression of HDAC6. Treatment with tubastatin A (TA), a highly selective HDAC6 inhibitor, or silencing of HDAC6 with siRNA decreased the expression of HDAC6. Moreover, TA or HDAC6 siRNA suppressed IL-6-induced EMT, as evidenced by decreased expression of α-SMA, Fibronectin and collagen I and preserved expression of E-cadherin in cultured HPMCs. Mechanistically, HDAC6 inhibition suppressed expression of transforming growth factor β (TGFβ) receptor I (TGFβRI), phosphorylation of Smad3, secretion of connective tissue growth factor (CTGF) and transcription factor Snail. On the other hand, pharmacological inhibition or genetic target of HDAC6 suppressed HPMCs proliferation, as evidenced by decreased optical density of CCK-8 and expression of PCNA and Cyclin E. And the migratory rate of HPMCs also decreased. Mechanistically, HDAC6 inhibition blocked the activation of JAK2 and STAT3. Conclusions: Our study illustrated that IL-6-induced deacetylase HDAC6 not only regulated IL-6 itself downstream JAK2/STAT3 signaling, but also co-activated the TGF-β/Smad3 signaling, leading the change of the phenotype and mobility of HPMCs. HDAC6 could be a potential therapeutic target for the prevention and treatment of peritoneal fibrosis.